Shape Evolutions in Fission Dynamics Within Time-Dependent Hartree-Fock Approach - Pancic, Marko; Qiang, Yu; Pei, Junchen; Stevenson, Paul (Frontiers in Physics, 2020)
We studied the nuclear shape evolutions in fission process of 240Pu by the time-dependent Hartree-Fock approach with various Skyrme forces. Calculations are performed for the later phase of the fission with large initial deformations toward the scission. We show that calculations with Skyrme forces with large surface energies and large symmetry energies can have extremely long fission evolution time. The symmetry energy plays a role in the evolution of neutron-rich necks. In addition, we also demonstrated the shape oscillations of fission fragments after the fission. We see that particularly the heavy near-spherical fragments have remarkable octupole oscillations.